The use of polygenic risk scores in pre-implantation genetic testing: an unproven, unethical practice - Forzano, Francesca; Antonova, Olga; Clarke, Angus; de Wert, Guido; Hentze, Sabine; Jamshidi, Yalda; Moreau, Yves; Perola, Markus; Prokopenko, Inga; Read, Andrew; Reymond, Alexandre; Stefansdottir, Vigdis; et al. (European journal of human genetics : EJHG, 2022)
Polygenic risk score analyses on embryos (PGT-P) are being marketed by some private testing companies to parents using in vitro fertilisation as being useful in selecting the embryos that carry the least risk of disease in later life. It appears that at least one child has been born after such a procedure. But the utility of a PRS in this respect is severely limited, and to date, no clinical research has been performed to assess its diagnostic effectiveness in embryos. Patients need to be properly informed on the limitations of this use of PRSs, and a societal debate, focused on what would be considered acceptable with regard to the selection of individual traits, should take place before any further implementation of the technique in this population.